Comparison of Dental Care Policies Before and During The COVID-19 Pandemic: A Literature Review - Ika Marta Nia; Inge Dhamanti (Poltekita : Jurnal Ilmu Kesehatan, 2022)
Dental care services have the highest risk of transmitting the COVID-19. Many countries and health organizations published policies or procedures for dental care services implementation during the COVID-19 pandemic. This study compared the dental care policies before and during the COVID-19 pandemic. This study narratively reviewed policies of dental care services before and during the COVID-19 pandemic. We searched for recommendations and guidelines on dental care policies by The Ministry of Health of Indonesia and The Centers for Disease Control and Prevention (CDC). The study result showed that the dental care policy before the COVID-19 pandemic explained infection preventive action in dental care facilities. Dental care policy during the COVID-19 pandemic explained COVID-19 preventive efforts and changes in the dental procedure like the use of teledentistry (to assess the dental condition of patients and follow up patients), postponing of elective surgeries, restricting the number of patients, screening COVID-19 for all patients, and implement of COVID-19 health protocol. The most striking differences among dental care policies before and during the COVID-19 pandemic were the pre-visit screening aspect (the use of teledentistry to assess dental condition) and the screening aspect (ensuring patients didn't have COVID-19 symptoms)